FIRE RETARDANTS (Web of Teachers: Inderscience Research, 2024)
As is known, all resinous polymers are flammable. Therefore, in order for polymer materials to meet fire safety requirements, flame retardants (fire retardants) are added to their composition. Additives must also meet high fire safety requirements.